IMPACT OF PHYSICAL ACTIVITY ON SYMPTOM SEVERITY AND QUALITY OF LIFE IN CHRONIC VENOUS DISEASE: A SYSTEMATIC REVIEW - Paweł Grzesikowski; Jakub Kubiak; Paulina Klich; Kinga Bekier; Hanna Nowicka (International Journal of Innovative Technologies in Social Science, 2026)
Objectives: Chronic venous disease is a common and progressive condition that affects the veins of the lower limbs and significantly reduces quality of life. It often leads to symptoms such as leg pain, edema, fatigue, and in advanced stages, skin changes and venous ulcers. This narrative review explores current research on the impact of physical activity on symptom severity and quality of life in patients with chronic venous disease.Methods: A literature search was conducted using PubMed and Google Scholar, focusing on studies published up to the year 2025, with particular emphasis on studies from 2015 to 2025. The following keywords were used: Chronic venous disease, chronic venous insufficiency, physical activity, symptom severity, quality of life.Conclusions: Results consistently show that physical activity is associated with reduced pain, edema, and fatigue, as well as improved physical functionality. Furthermore, physical activity was also shown to improve quality of life. Despite the positive impact of physical activity, many patients do not meet physical activity guidelines. Physical activity is an effective and low-cost approach to improving both symptom severity and quality of life in patients with chronic venous disease; however, clinical guidelines should aim to improve long-term adherence.